Willingness to pay for conservation among users of Matang Mangrove Forest Reserve, Perak, Malaysia - Ramli, Fatin (2017)
Mangrove forests provide important tangible and intangible benefits to local communities in the form of socioeconomic development opportunities such as fishing, ecotourism, and biodiversity conservation. Matang Mangrove Forest Reserve (MMFR) is chosen as the study site because it’s the best mangrove management in the world. However, the ecosystem services provided by the mangrove forest are undervalued. This study determined the direct users’ perception towards conservation of mangroves. Respondents were asked to state their level of importance by using the five-point interval scale with ten statements on why mangrove forest needs to be conserved. The method used to explore the dimensions was the exploratory factor analysis. The factors that affected the willingness to pay (WTP) for conservation fee of MMFR were also identified using the contingent valuation method (CVM). The double bounded dichotomous choice (DBDC) CVM was applied to estimate the WTP value for the conservation fee among respondents. A total of 685 direct users were purposively selected consisted of 300 fishermen and 385 visitors as respondents. Two factors were extracted with the eigenvalues of above 1.0 and the total variance of 61.12%. The common themes were identified and derived as perception dimensions. The findings revealed that the theme of perception was that sustainable ecosystem services appeared as the strongest perception followed by the biodiversity of flora and fauna. Results from DBDC showed that the fishermen’s WTP was significantly influenced by their ethnic and income, while visitors’ WTP was affected by age, marital status, ethnic, tax payment, income, the perception on biodiversity of flora and fauna and on sustainable ecosystem services. Assessing the economic value of mangrove forest ecosystem provides useful information to policy makers in the decision making process with regard to land use options. The majority of the respondents were willing to pay with the bid offered due to biodiversity conservation and preservation of MMFR and a minority of the respondents were unwilling to pay with the bid offered because they felt that the conservation cost should be borne by the government. Therefore, the average WTP of DBDC for the conservation fee is about MYR15.46 and MYR11.82 per person per year for fishermen and visitors, respectively. The total economic value of for the conservation of MMFR was estimated at MYR136,805.54 for fishermen and MYR566,662.62 for visitors. The values may be used to support fisheries department, natural-based conservation, Pusat Eko-Pelajaran Hutan Paya Laut Matang and MMFR management through financial resources to sustain the ecosystem services, especially for the use of direct users. Thus, respondents’ dimension of perception towards conservation of mangroves, factors that affected WTP for conservation fee of MMFR and WTP values are crucial to assist decision makers as well as a guideline to policy makers in sustaining the long term social benefits for mangrove forest management in Malaysia. Future work should focus on estimating the total economic value for the whole MMFR in ensuring sustainable management for the future generation.